Tax Evasion Perception Among Students: Gender, Religiosity, Taxation System, and Tax Rates Influence - Wardeni, Endah Kusuma; Nurasik (Indonesian Journal of Islamic Studies, 2023)
This study investigates the factors influencing students' perceptions of tax evasion, specifically examining the impact of gender, religiosity, taxation system, and tax rates. Using multiple linear regression analysis with SPSS, the research findings reveal that gender and religiosity do not significantly influence students' perceptions of tax evasion. However, the taxation system significantly affects their perceptions, with tax rates also demonstrating a significant influence. These results provide valuable insights for students, potential taxpayers, and policymakers regarding the factors that shape perceptions of tax evasion, aiming to promote tax compliance and deter tax evasion behavior. Highlights: Gender and religiosity have no significant impact on tax evasion perception. The taxation system plays a crucial role in shaping students' perceptions of tax evasion. Tax rates are a significant influencing factor in students' perceptions of tax evasion. Keywords: Tax evasion, Perception, Gender, Religiosity, Taxation system, Tax rates